Polyodon spathula – a Specie of Interest for Pisciculture in Eastern European Countries, Study on Meat Quality and Environmental Impact in Romania - Cristina Simeanu; Bogdan-Vlad Avarvarei; Daniel Simeanu (Research Aspects in Biological Science Vol. 5, 2022)
Paddlefish was introduced in the East part of Europe since 1974, but in some countries in this region the growth of this specie has only increased in the last 20 years. Continuous increase of the number of Polyodon spathula has created the premises for a closer analysis of the impact of this specie on the environment in those regions, the study of morphological and productive characteristics and the quantitative and qualitative characteristics of meat from paddlefish populations in Eastern Europe. The Polyodon spathula rearing is recommended by its high meat nutritional values, which are in close relationship with its high protein, unsaturated fat, vitamin, and mineral contents. Polyodon spathula pisciculture has the potential to benefit producers financially while also helping to maintain and conserve sturgeon in their natural habitats. Polyodon spathula has a low ecological risk in several Romanian fish populations, due to its planktonofag eating, which makes it a non-competitor for native fishes. Furthermore, the genetic difference with indigenous acipenseride makes the process of introgression impossible. Polyodon spathula may be suggested for use in different aquaculture farms in order to obtain high-quality fish meat and to enhance the economic value of Romanian fish meat production, despite the fact that there is currently no conclusive data regarding its negative impact on the autochthonous ichtyofauna and its role in other fish extinctions or dramatic decreases in their numbers.